Ways of introduction of quarantine harmful organisms Spodoptera eridania, S. frugiperda, S. littoralis and S. litura - Sikura, O.; Hunchak, V.; Solomiichuk, Ì. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. Determine possible ways of introduction of quarantine harmful organisms S. eridania, S. frugiperda, S. littoralis and S. litura into the territory of Ukraine.Methods. For each studied organism, the geographical distribution and spectrum of their host plants were taken into account. According to the data of the State Statistics Service of Ukraine, it was found out whether imported products, with which the investigated pests can be associated, arrive on the territory of Ukraine from the areas of their distribution. The possibility of penetration of quarantine species of scoops by natural means and the biological features of their distribution were evaluated.Results. It was established that the main ways of penetration of the studied organisms are their distribution on the leaves of host plants with plant products, with vegetable products, planting material and decorative plants, plants in pots in the stages of eggs, larvae or pupae. The spread of pests naturally occurs due to imago flights over considerable distances. In addition, the presence of air currents can help the spread of quarantine scoops to even greater distances from the territories where their development takes place.Conclusions. Scoop butterflies are naturally able to migrate long distances. The introduction of pests of the genus Spodoptera takes place in the stages of eggs, larvae or pupae, mainly with vegetable products, ornamental plants and soil mixtures imported into Ukraine. During a full-scale war between Russia and our countrythe presence of Russian military equipment in the partially occupied southern regions of Ukraine makes it possible for Spodoptera litura Fabr., which is common in the south of the Russian Federation, to enter Ukraine. Also, military equipment from those NATO countries where quarantine pests of the genus Spodoptera are widespread enters Ukraine.